Intervensi Negara Dalam Pengawasan Kepatuhan Syariah Pada Perbankan Syariah Berdasarkan Prinsip Keadilan Dan Maslahah Mursalah - Amira; Hannani Yunus (Al Rikaz: Jurnal Ekonomi Syariah, 2026)
This study aims to critically analyze the limitations and implementation of state intervention in Islamic banking operations through the lens of the principles of justice and the concept of maslahah mursalah. The scope of this research specifically focuses on state intervention in the function of Sharia compliance supervision carried out by financial authorities (the Financial Services Authority/OJK and Bank Indonesia) through the integration of religious authority fatwas into positive law. The research employs a qualitative method with a library research approach, examining statutory regulations and literature on Islamic economic law. The findings indicate that state intervention in Sharia compliance supervision constitutes a legitimate manifestation of the tanzhim (regulatory) function aimed at protecting public welfare (al-maslahah al-ammah) and safeguarding the wealth of society (hifz al-mal). An ideal form of intervention should be proportional, whereby the state is obligated to provide legal certainty for Sharia compliance instruments without stifling innovation in Islamic banking products or imposing risk standardization based on conventional and exploitative paradigms